Transgenderism in the Novella and Film Albert Nobbs - Varga, Dejan (Anafora, 2023)
Considering narratology and its relation to other analytical and methodological models within the humanities, the paper analyzes the position of the characters of the novella Albert Nobbs (1918) by Irish writer George Moore in relation to its film adaptation directed by Rodrigo Garcí (2011). Since the two different media provide different narratological insights into the story, the analysis starts with the assumption that the identity of the characters, primarily the heroine, is shaped differently in the film than in the literary text. This difference is most noticeable in the category of gender identity, male/female relationships, but also in the presence of latent homosexuality (lesbian craving), which certainly seems radical as the operation takes place in the nineteenth century. Along with the contemplations of contemporary theoreticians of gender identity, the paper will attempt to analyze two narratologically different approaches to identity formation, which leaves the impression that the identity of Alberto Nobbs is reflected in all kinds of fractures and circumstances as a perpetual quest for stability that often results in conflict with oneself, as well as the conservative society surrounding him.